PENGARUH KEGIATAN EXTRA FEEDING DAN POLA ASUH ORANGTUA TERHADAP KEMANDIRIAN ANAK - TASU’AH, NENENG (Jurnal Pendidikan Usia Dini, 2013)
The aims of this research was to understand comprehensively the influence of extrafeeding activities and parenting toward independence children (Experiment in student class I atSDN Pejaten Barat, South Jakarta, 2013). The method usedin this studyis the experimentalmethod with Children independen ceas the main problem which is the dependent variable. Whilefirst independent variableis the Extra Feeding activity (in this study is Cooking Fun activities andactivities Role Playing) and the second independent variable is the parenting parent (in this studyis the pattern of otoritarian parenting, democratic and permissive). In this study the samplingtechniqueto be used the multi stage cluster sampling. The sample In this study is in twoelementary school SDN 12 and SDN Pejaten Barat 10 each class I have a number of students ofapproximately 30 students so that a total number of 60 students, but at the time of the study theresearchers only select students based on parenting question naire results by category otoritarianparenting, permissive, democratic and 10 students respectively so that the samplein this studywere 30 students as control class in SDN Pejaten Barat 10 and 30 students as an experimentalclass at SDN Pejaten Barat 12. This study is a design experiment with designs fatorial 2x3.Therefore, data analysis using ANOVA two lines, iftested the difference, followed by Tukey'stestor Scheffe testto determine which one is higher. The finding lead to the recommendation touse extra feeding activities and parenting to improving independence children. And teacher shouldbe free to use learning methods especially extra feeding activities. Keyword: extra feeding activities, parenting, and independence children Penelitian ini bertujuan untuk memahami secara komprehensif pengaruh kegiatan extrafeeding dan pola asuh terhadap kemandirian anak di SDN Pejaten Barat, Jakarta Selatan, 201.Variabel independen pertama adalah aktivitas extra feeding (kegiatan Fun cooking dan kegiatanRole Playing) dan variabel independen kedua adalah pola asuh orang tua (pola asuh otoritarian,demokratis dan permisif). Sampel penelitian adalah SDN 12 dan SDN Pejaten Barat 10, masingmasing kelas I memiliki jumlah siswa sekitar 30 siswa sehingga jumlah total 60 siswa, penelitimemilih siswa berdasarkan hasil pengasuhan berdasarkan kategori pola asuh otoritarian, permisif,demokratis dan masing-masing 10 siswa sehingga sampel penelitian ini adalah 30 siswa sebagaikelas kontrol di SDN Pejaten Barat 10 dan 30 siswa sebagai kelas eksperimen di SDN PejatenBarat 12. Penelitian ini menggunakan eksperimen dengan desain penelitian 2x3 fatorial. Olehkarena itu, analisis data menggunakan ANOVA dua jalur, uji perbedaan, diikuti oleh test TukeyScheffe testto untuk menentukan mana yang lebih tinggi. Temuan menyebabkan rekomendasiuntuk menggunakan kegiatan extra feeding dan pengasuhan anak-anak untuk meningkatkankemandirian. Guru harus bebas untuk menggunakan metode pembelajaran kegiatan makanterutama extra feeding. Kata Kunci: aktivitas extra feeding, pola asuh orang tua, dan kemandirian anak